Measuring social media impact on Impulse Buying Behavior - Prakash Singh; Bhuvanesh Kumar Sharma; Lokesh Arora; Vimal Bhatt (Cogent Business & Management, 2023)
AbstractIn today’s ever-evolving business landscape, understanding the shifting buying behaviors of consumers has become a formidable challenge for businesses worldwide. To navigate these changes successfully, businesses are increasingly turning to Social Networking Sites (SNS) to attract, connect with, and engage customers profitably. However, analyzing the influence of social networking sites on Impulse Buying Behavior (IBB) among customers is challenging for businesses and significant for their sustainability in the market. The main purpose of the present research work is to analyze the influence of social media on Impulse Buying Behavior (IBB) among customers in Saudi Arabia. The present quantitative study was conducted by sending a survey questionnaire to 342 Saudi Arabian consumers who are also users of social media. Data analysis was done using the PLS-SEM technique using smart PLS 4.0 software. The findings of the study suggested that Social Media Advertising (SMA) significantly influenced Impulse Buying Intention (IBI), but no effect was reported by the Social Media Community (SMC) on Impulse Buying Intention (IBI). However, the overall model explained 50 percent Impulse Buying Intention (IBI) and 33 percent Impulse Buying Behavior (IBB). The study will enable marketers, scholars, and researchers to understand the concept of Impulse buying by offering managerial implications and future research directions.